Algorithmic model of information technology for analysis and forecasting of commodity market conditions - Лисицкий, Василий Лаврентьевич; Нгуен, Тан Мань (Eastern-European Journal of Enterprise Technologies, 2015)
The paper presents the results of research in the field of mathematical modeling of the formation dynamics of the commodity market conditions, taking into account market pricing mechanisms, as well as the effect of the dynamic processes occurring in the economic and social environments. Using the methods of system dynamics, an algorithmic model for forecasting the dynamics of commodity market conditions was developed. The modeling algorithm of the simulation model of the commodity market functioning, which determines the functional and behavioral characteristics of the developed information technology for analysis and forecasting of the commodity market conditions was designed. The method of adjusting the simulation model to the real commodity market was proposed. Using statistical and current information on the commodity market functioning, the user interface of the information technology allows determining appropriate parameters, building time series for forecast trajectories of changes in the commodity market characteristics, visually analyzing trends in the commodity market conditions, single out trend components of the time series, predicting the trend direction change moment. In addition, the developed information technology allows to carry out the scenario method for analysis and forecasting of the commodity market conditions.